The Development of Academic Advising to Enable Student Success in South Africa (Journal of Student Affairs in Africa, 2021)
Universities promote social justice by improving student success; a university degree is one of the most powerful tools to change the economic prospects of students, their families, and communities. For students to succeed, it is vital that they are connected to the wide range of support services in a meaningful way. Unfortunately, many students (especially first-generation students) find it difficult to connect to university environments that are complex and that are often not optimally coordinated.  International and national research show that academic advising plays a critical role in improving student engagement and success by facilitating better coordination and integration of support. Academic advising provides students with relevant information, facilitates their conceptual understanding of the university, and allows students the opportunity to form a meaningful relationship with the institution through an advisor and by means of various advising initiatives. This paper shares international perspectives on the critical importance of academic advising for student success. Building on these perspectives, we reflect on the development of academic advising in South Africa and on its potential for enhancing student success in our context. We provide an institutional perspective by sharing the journey of the University of the Free State. In doing so, we show the positive impact of advising before and during the pandemic and we conclude with lessons for the future of academic advising in the South African context.
Keywords: academic advising; student success; higher education; South Africa; University of the Free State